2003
DOI: 10.1542/peds.111.3.e227
|View full text |Cite
|
Sign up to set email alerts
|

Pediatrician Beliefs About Spirituality and Religion in Medicine: Associations With Clinical Practice

Abstract: ABSTRACT. Objectives. Identify pediatrician (faculty and resident) beliefs about spirituality and religion (SR) in medicine and the relationship of those beliefs to SR behavior and experiences in clinical practice.Methods. A self-report questionnaire was administered to full-time pediatric faculty (N ‫؍‬ 65) and residents (N ‫؍‬ 56) of an urban children's hospital affiliated with a school of medicine. The response rate was 70.8% among faculty (n ‫؍‬ 46) and 78.6% among residents (n ‫؍‬ 44). Respondents indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 26 publications
(25 reference statements)
1
41
0
Order By: Relevance
“…This finding is in agreement with data from Armbruster et al (2003), who showed that paediatric residents were less likely to enquire about religious beliefs in comparison to faculty physicians (24.4% vs. 6.8%), highlighting the importance of training in how to have such discussions.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding is in agreement with data from Armbruster et al (2003), who showed that paediatric residents were less likely to enquire about religious beliefs in comparison to faculty physicians (24.4% vs. 6.8%), highlighting the importance of training in how to have such discussions.…”
Section: Discussionsupporting
confidence: 91%
“…Because there is no other study in the literature that measures the same study variables in a Muslim population, the sample size was determined based on previously published questionnaire-based surveys of religiosity among physicians in other populations (Luckhaupt et al 2005;Ellis et al 1999;Armbruster et al 2003). A convenient sample size was estimated to be two hundred.…”
Section: Methodsmentioning
confidence: 99%
“…Clinicians have already begun to use formal ''spiritual history'' templates developed for incorporation into the clinical encounter [63]. Although one study found that while only one fourth of pediatric attending physicians and 7% of pediatric residents routinely inquired about patient/family religious issues, nearly three quarters of these attending physicians and 90% of these residents felt that religious beliefs positively impact health, and roughly 90% of both groups felt religious issues were relevant to pediatric medicine [64]. The connections demonstrated between mental health and religion/spirituality call for clinicians to get to know about the role of religion/spirituality in their patients' lives.…”
Section: Discussionmentioning
confidence: 99%
“…Spirituality, religion, and prayer can be topics avoided in medicine, especially by conventionally trained physicians who do not wish to offend their patients or are uncomfortable discussing this topic. 11 However, for millennia, religion and healing have been intertwined. Patients often pray for their own health and the health of others.…”
Section: Resultsmentioning
confidence: 99%